2021
DOI: 10.1101/2021.09.27.461985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The transcriptomic signature of cyclical parthenogenesis

Abstract: Cyclical parthenogenesis, where females can engage in sexual or asexual reproduction depending on environmental conditions, represents a novel reproductive phenotype that emerged during eukaryotic evolution. The fact that environmental conditions can trigger cyclically parthenogens to engage in distinct reproductive modes strongly suggests that gene expression plays a key role in the origin of cyclical parthenogenesis. However, the genetic basis underlying cyclical parthenogenesis remains understudied. In thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…In accordance with our results, gynogenetic P. formosa was shown to underexpress meiosis-related genes, including sbk3, setd7 and stk32c, compared to its supposed sexual ancestors (19). Similarly, in cyclically parthenogenetic Daphnia, meiosis-related genes, including genes related to the spindle assembly checkpoint, the APC, and meiosis chromosome segregation, were upregulated during sexual reproduction (71). In particular, spo11, which encodes a topoisomerase involved in chromosomal recombination during the meiotic prophase, was also described as an important player in the meiosis-to-parthenogenesis transition in pea aphid (87), although it was not reported in asexual P. formosa (19).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with our results, gynogenetic P. formosa was shown to underexpress meiosis-related genes, including sbk3, setd7 and stk32c, compared to its supposed sexual ancestors (19). Similarly, in cyclically parthenogenetic Daphnia, meiosis-related genes, including genes related to the spindle assembly checkpoint, the APC, and meiosis chromosome segregation, were upregulated during sexual reproduction (71). In particular, spo11, which encodes a topoisomerase involved in chromosomal recombination during the meiotic prophase, was also described as an important player in the meiosis-to-parthenogenesis transition in pea aphid (87), although it was not reported in asexual P. formosa (19).…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that members of the same gene family can be up-or downregulated, such as members of the zona pellucida and F-box families. Such divergent expression, also reported in Daphnia (71), may suggest functional divergence among members of the same multigenic families.…”
Section: Discussionmentioning
confidence: 66%
“…Among these emerging systems, Daphnia has excellent potential for genomic functional studies, largely thanks to the wealth of knowledge accumulated from decades of research on their evolution/adaptation, ecology, toxicology, phenotypic plasticity, and response to environmental factors (Altshuler et al 2011). Since the development of first-generation Daphnia genomic tools (Colbourne et al 2011), researchers have identified a large number of candidate genes responsible for various biological processes, such as adaptation to freshwater salinization (Wersebe and Weider 2023), heavy metal contamination (Shaw et al 2007), the origin of obligate parthenogenesis and cyclical parthenogenesis (Xu et al 2015; Xu et al 2022; Huynh et al 2023; Snyman and Xu 2023), and adaptation to ecologically distinct habitats (Ye et al 2023), which are ready to be further interrogated for functional insights.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggests that the origin of obligate parthenogenesis from meiosis is likely caused by the downregulation of key meiosis and cell cycle genes, and an upregulation of metabolism. Interestingly, when comparing the gene expression patterns between early subitaneous egg and early resting egg production within individual CP D. pulex and D. pulicaria isolates (Figure 2B) , meiosis and cell cycle genes were also found to be downregulated while metabolic, and biosynthesis genes were upregulated in early subitaneous egg development (i.e., parthenogenesis) compared to resting egg production (i.e., meiosis) in both species (Huynh et al . 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggests that the origin of obligate parthenogenesis from meiosis is likely caused by the downregulation of key meiosis and cell cycle genes, and an upregulation of metabolism. Interestingly, when comparing the gene expression patterns between early subitaneous egg and early resting egg production within individual CP D. pulex and D. pulicaria isolates (Figure 2B), meiosis and cell cycle genes were also found to be downregulated while metabolic, and biosynthesis genes were upregulated in early subitaneous egg development (i.e., parthenogenesis) compared to resting egg production (i.e., meiosis) in both species (Huynh et al 2021). Together, the results from these two transcriptomic studies strongly suggest that parthenogenesis in both OP (resting egg production) and CP (subitaneous egg production) isolates are associated with a downregulation of meiosis and cell cycle genes and an upregulation of metabolic and biosynthesis genes, which may play essential roles in triggering parthenogenesis.…”
Section: Introductionmentioning
confidence: 99%